Status of liver stiffness following directly acting antiviral treatment in patients with chronic hepatitis C: A Nepalese study - Sharma, Dilip; KC, Sudhamshu; Shrestha, Ananta; Jaishi, Bikash (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: Chronic hepatitis C is one of the leading causes of chronic liver disease in our country. With the introduction of directly acting antivirals, many patients are benefitted these days. Transient elastography is one of the newer technologies for measuring liver stiffness and quantifying liver fibrosis and has excellent accuracy for the diagnosis of fibrosis in patients with chronic hepatitis C. Our study analyzes changes of liver stiffness and its associated factors in patients with chronic hepatitis C treated with directly acting antivirals (DAAs). Materials & Methods: One hundred and seven patients with chronic hepatitis C, who were treated with DAAs (Sofosbuvir 400 mg and velpatasvir 100mg) and have significant fibrosis (>7.0 kPa) at baseline were included. Liver stiffness was measured at the time of enrollment, and after completion of DAAs with fibroscan and changes of stiffness and its associated factors were analyzed. Results: The study showed significant decrease in liver stiffness at the end of treatment, which continued after treatment only in patients who achieved a sustained virological response. Conclusion: Liver stiffness decreased following 12 weeks of successful DAAs therapy in patients with chronic hepatitis C at the end of treatment who achieved sustained virological response.